2014
DOI: 10.1101/sqb.2014.79.024950
|View full text |Cite
|
Sign up to set email alerts
|

The Macaque Face Patch System: A Window into Object Representation

Abstract: The macaque brain contains a set of regions that show stronger fMRI activation to faces than other classes of object. This "face patch system" has provided a unique opportunity to gain insight into the organizing principles of IT cortex and to dissect the neural mechanisms underlying form perception, because the system is specialized to process one class of complex forms, and because its computational components are spatially segregated. Over the past 5 years, we have set out to exploit this system to clarify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The preferential responses to human faces compared to non-human faces is in line with a recent human functional magnetic resonance imaging (fMRI) study, in which multivariate patterns of activity throughout the ventral TC were found to correlate with behavioral judgments of biological similarity of the same stimuli (i.e., monkeys and mammals versus insects and birds) 59 . Moreover, two electrophysiological studies in the macaque brain have shown faster responses of neurons to primate faces compared to nonprimate animal faces 60 or a change in species selectivity across different patches of face-selective areas 61 . Our findings along with these studies may explain the behavioral observations of conspecific advantage in face recognition; that is, humans and other primates recognize members of their own species more readily than faces of other species 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…The preferential responses to human faces compared to non-human faces is in line with a recent human functional magnetic resonance imaging (fMRI) study, in which multivariate patterns of activity throughout the ventral TC were found to correlate with behavioral judgments of biological similarity of the same stimuli (i.e., monkeys and mammals versus insects and birds) 59 . Moreover, two electrophysiological studies in the macaque brain have shown faster responses of neurons to primate faces compared to nonprimate animal faces 60 or a change in species selectivity across different patches of face-selective areas 61 . Our findings along with these studies may explain the behavioral observations of conspecific advantage in face recognition; that is, humans and other primates recognize members of their own species more readily than faces of other species 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…This permutation logic-based coverage of all possible connectivity-patterns can mechanistically account for why researchers reported all sorts of interesting cells in the brain that corresponded to some kind of specific stimulus or multiple stimuli (e.g., syringes, peanuts, faces, hands, the actress Halle Berry, or a nest) or a category of items (e.g., dogs vs. cats, or people vs. other objects; Rolls et al, 1979; Logothetis and Sheinberg, 1996; Fried et al, 1997; Freedman et al, 2003; Hampson et al, 2004; Gross, 2005; Quiroga et al, 2008; Bowers, 2009; Tsao, 2014). Although combining simple stimulus-features from sensory organs for higher cognition were often postulated and reported (Buck and Axel, 1991; Yeshurun and Sobel, 2010; Fu et al, 2015), findings of some cells in a given site which responded to multiple stimuli (as the literature intermittently described in bits and pieces) have reinforced the popular but undue impression that somehow convergence and combination occurred but in a stochastic and random fashion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the fusiform face area FFA, initially conceptualized as one area, decomposes into multiple areas (FFA1 and FFA2) when scanning at a finer spatial resolution [50,51]. Data from human imaging and monkey electrophysiology support a hierarchical model with an increase of the complexity, invariance, and perceptual subjectivity of the represented features [49,[53][54][55][56][57][58][59][60][61]. Areas higher up in the computational hierarchy, corresponding to more anterior regions in ventral OTC in human cortex, represent stimuli such as faces and words in a more holistic, less part-based manner and with higher levels of invariance for image transformations.…”
Section: Computational Hierarchymentioning
confidence: 99%